Restrição financeira, tangibilidade e capital de giro: como as empresas brasileiras investem - Toledo, Rafael Ramos de (2016)
Using panel data over 15,000 among listed and unlisted Brazilian companies observations in the period from 2010 to 2014, the present study analyzed the presence of credit constraint and its relation to investments in fixed assets and the role of the working capital as a management tool in investment decisions in fixed assets. For this purpose, we used two-basic methodologies: the study of Almeida and Campello (2007), which was innovative by including variables that controls some of the biggest criticisms in literature related to the credit constraint and the study of Ding, Guariglia and Knight (2011), which analyzed the ratio of working capital investment with investment in fixed assets. The findings of this study show that, in general, Brazilian companies suffer from credit constraints and that companies that invest more in working capital showed lower sensitivity of investment in fixed assets to cash flow, however, them are not able to translate this into higher investment rates.